Decadal changes in habitat characteristics influence population trajectories of southern elephant seals. (12th July 2017) - Hindell, Mark A.; Sumner, Michael; Bestley, Sophie; Wotherspoon, Simon; Harcourt, Robert G.; Lea, Mary‐Anne; Alderman, Rachael; McMahon, Clive R.
Abstract: Understanding divergent biological responses to climate change is important for predicting ecosystem level consequences. We use species habitat models to predict the winter foraging habitats of female southern elephant seals and investigate how changes in environmental variables within these habitats may be related to observed decreases in the Macquarie Island population. There were three main groups of seals that specialized in different ocean realms (the sub‐Antarctic, the Ross Sea and the Victoria Land Coast). The physical and climate attributes (e.g. wind strength, sea surface height, ocean current strength) varied amongst the realms and also displayed different temporal trends over the last two to four decades. Most notably, sea ice extent increased on average in the Victoria Land realm while it decreased overall in the Ross Sea realm. Using a species distribution model relating mean residence times (time spent in each 50 × 50 km grid cell) to 9 climate and physical co‐variates, we developed spatial predictions of residence time to identify the core regions used by the seals across the Southern Ocean from 120°E to 120°W. Population size at Macquarie Island was negatively correlated with ice concentration within the core habitat of seals using the Victoria Land Coast and the Ross Sea. Sea ice extent and concentration is predicted to continue to change in the Southern Ocean, having unknown consequences for the biota of the region. The proportion of Macquarie Island females (40%) utilizing the relatively stable sub‐Antarctic region, may buffer this population against longer‐term regional changes in habitat quality, but the Macquarie Island population has persistently decreased (−1.45% per annum) over seven decades indicating that environmental changes in the Antarctic are acting on the remaining 60% of the population to impose a long‐term population decline in a top Southern Ocean predator. Abstract : This study explains the dramatic long‐term decrease in an elephant seal population (over 50% in seven decades). The decrease is related to long‐term increases in the regional sea ice extent in winter in two of the population's core habitats.